PARALELIZAÇÃO DE APLICAÇÕES COM ALTO CUSTO COMPUTACIONAL - Padoin, Edson L.; Borges, Pedro A. P.; Dill, Sergio L.; Borges, Roberto S.; Rodrigues, Alessandro; Colatto, Carlos E.; Wiest, Roberto (Salão do Conhecimento, 2013)
Resumo